DANGER IN THE BLOOD” BSI AND CURRENT TREND IN ANTIMICROBIAL RESISTANCE - RAAKHEE BABY.THANANKI,; HEMA PRAKASH KUMARI,; S. SUBBARAYUDU, (International Journal of Pharma and Bio Sciences, 2014)
It’s a leading cause of death. It’s a major source of health care costs, adding days or weeks to the hospital stays, no one fully understands how best to fight it. Bacteremia may be self limiting or life threatening. So, correct and accurate antibiotics to be employed to understand the common pathogens and their resistance pattern time -to-time. The present study was undertaken to know the pathogens causing Blood stream infections and incidence of multidrug resistance (MDR). Altogether 776 blood samples were investigated during the working period between January to December, 2012 at microbiology laboratory, ASRAM hospital, Eluru. A total of 191 (24.6 %) blood samples were found to be culture positive. CoNS (50 %) were the predominant isolate, followed by Staphylococcus aureus (44.56 %) and Klebsiella pneumoniae (38.38 %). Analysis of the samples showed that Bacteremia was common in males when compared to females. Antimicrobial drug resistance is a major problem in India. During the last few years a lot of attention was being paid to microbial resistance. There have been many debates but the outcomes are negative. This study shows that a good percentage of people were infested by multi-drug resistant bacterial agents.